Participio de presente latino tardío y medieval entre norma y habla - Mesa Sanz, Juan Francisco (ELUA: Estudios de Lingüística. Universidad de Alicante, 2004)
The use of present participle in the literary texts and its problems of translation to a Romanic language manifest the syntactical development of that verbal form; in the same way, they show the tension from its double nature: verbal and adjectival. That tension was broken in the Late and Medieval Latin: while the development «vulgar», actual germ for the Romanic languages, marked the adjectival, at the same time in literary texts was used as verbal form, even as predicate. That use has been called «written vulgarism». It was its origin in the literary spoken properly, cause of the great productivity and economy as expresive tool. Nevertheless, latest centuries of Empire knew a group of phaenomena that acelerated theses verbal uses. First at all, the school into a environment of poor culture caused that «syntactic hypercorrection», an actual «scholar vulgarism», born in the sermo scolasticus.